Caracterização Estrutural, Morfológica e Magnética da Dupla Perovsquita Ca2MnReO6. - Souza, Danilo Oliveira de (2009)
Compounds with structure of ordered double perovskyte, A2B’B’’O6 (A being an alkaline-earth and B being a transition-metal in alternate sites) have attracted interest of the researches because their strong correlated structural and magnetic properties. Moreover, they are suitable candidates to produce devices with great application in spin-electronic, named “spintronics”. The special group of these compounds, the Re-based ordered double perovskites, i. e., the double perovskites where the B’’ sites are occupied by Re atoms, have been studied since 1961. However, it was only at the last decade, in spintronics framework, that these compounds have received a special attention. This work describes the synthesis and characterization of Ca2MnReO6 ordered double perovskyte. It does that by marking out sintered procedures and the structural and magnetic properties, which have been investigated by synchrotron x – ray powder diffraction, x – ray absorption spectroscopy and magnetic measurements. SEM images have shown homogeneity phase composition, the morphology and size of the ceramic grains. The Rietveld refinement has revealed a monophase compound and it was used to determinate the lattice parameters. The x – ray absorption spectroscopy agrees with the diffraction results and point to a formal (or effective) valence for Re atoms as +5,5. An interpretation of this result is that there exists a mixed valence for Re atoms, balanced by mixed valence of Mn atoms. The magnetic susceptibilities measurements were performed with temperature variation and have pointed a paramagnetic phase transition in 120 K with a spin glass type state below this value. An explanation for the magnetic result may be given with assumption of low contribution magnetic moment of Re atoms, or a nonexistent one.